Edward II - Phillips, J. R. S. (Yale English monarchs., 2010)
This biography does not present Edward II as a heroic or successful king: his deposition after a turbulent reign of nearly twenty years is proof enough that it went terribly wrong. But Seymour Phillips' scrutiny of the multitude of available sources shows that a richer picture emerges, in line with the complexity of events and of the man himself. If Edward II was not a successful king, he was not fundamentally different in many ways from most English monarchs. The biography strikes a deft balance, taking full account of the problems the king faced in England, Scotland, and Ireland and in his relations with France. It also tackles the contentious issue of whether Edward II did not die in 1327, murdered under barbaric circumstances, but lived on as a captive in England and then a wanderer on the Continent.--from publisher description.